Ta'arudh Mafsadatain dalam Tinjauan Tasawuf: Pemikiran Abdul Wahab al-Sya'rani Tentang Mujahadat al-Nafs - Karimah, Yunita Hikmatul; Yaqin, Ainul; Rozi, Fathur (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
This paper discusses Sufi behaviour in mujahadat al-nafs, which is one of the mediators to achieve shidq al-tawajjuh. In its implementation, the practice of mujahadat al-nafs is considered problematic among scholars. The reason is that someone who does this practice is required to take things that contain h}araj or harm themselves, and of course this is considered contrary to the principles of sharia. This research aims to examine the practice of mujahadah in the review of Sufism in the perspective of ‘Abd Al-Wahhab Al-Sha'rani. The method used is qualitative research with a descriptive-analytical approach. The results of this study indicate that the practice of mujahadah carried out by a Sufi is in fact not at odds with the lines of shari'a. The reason is that if it reaches the level of mujahadah, the Sufi will not be able to do it. The reason is that if it reaches the limit of idhthirar (urgency), the culprit will stop the practice of mujahadat al-nafs and not cause something that can eliminate his life. On the other hand, through the point of view of ta'arudh al-mafsadatain, Al-Sha'rani's view assesses the practice of mujahadah is still within the principle of using akhaff al-mafsadatain (the lightest mafsadah). This means that the consequences of mafsadah/damage in the form of pain received by the physical body are not comparable to the spiritual mafsadah in the form of negligence in mujahadah, which is part of the continuity of the suluk journey. With this argumentation, perfection in worship, including consistency in musyahadah, is part of what is worthy of obligatory matters for Sufis.